Immunohistochemical Investigation of Metastasis-Related Chemokines in Deep-Infiltrating Endometriosis and Compromised Pelvic Sentinel Lymph Nodes. (December 2015) - Borrelli, G. M.; Abrão, M. S.; Taube, E. T.; Darb-Esfahani, S.; Köhler, C.; Kaufmann, A. M.; Chiantera, V.; Mechsner, S.
Endometriosis is a prevalent benign disease, despite sharing several similarities with malignancies, such as the possibility of lymphatic spread. In malignancies, chemokines play a sovereign role in the process of metastasis. Metastasis-related chemokine axes have not yet been assessed in deep-infiltrating endometriosis (DIE), and this investigation was the aim of our study. The expression of these chemokines was investigated by immunohistochemistry in rectovaginal DIE lesions and in matched pelvic sentinel lymph nodes (PSLNs) of patients with endometriosis (n = 27), and their expression in the eutopic endometrium (EE) of endometriosis-free women (n = 20) was used as controls. Their staining pattern in rectovaginal DIE, in endometriotic lesions affecting the PSLN as well as in the EE of patients without endometriosis was characterized for the first time. Overall, these chemokines were highly expressed in DIE and endometriosis in PSLN. Chemokines might be involved in the spread of endometriosis and should be further investigated.